2017
DOI: 10.1016/j.devcel.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Skin and Its Regenerative Powers: An Alliance between Stem Cells and Their Niche

Abstract: Tissues have a natural capacity to replace dying cells and to heal wounds. This ability resides in resident stem cells, which self-renew, preserve, and repair their tissue during homeostasis and following injury. The skin epidermis and its appendages are subjected to daily assaults from the external environment. A high demand is placed on renewal and regeneration of the skin’s barrier in order to protect the body from infection and dehydration and to heal wounds. This review focuses on the epithelial stem cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
336
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(346 citation statements)
references
References 108 publications
(207 reference statements)
5
336
0
5
Order By: Relevance
“…Mammalian HF undergoes a lifetime cyclic regeneration, and several discoveries have increased our understanding on the regulation of this significant model of organ regeneration, both at individual HF level, through coordinated interactions with other cells at the HFSC niche or molecular signaling across adjacent HF across the tissue (Widelitz & Chuong, ; Gonzales & Fuchs, ; Guasch, ). Here, we now show that within a single HF, HFSC associates with LV capillaries, starting from developmental HF stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammalian HF undergoes a lifetime cyclic regeneration, and several discoveries have increased our understanding on the regulation of this significant model of organ regeneration, both at individual HF level, through coordinated interactions with other cells at the HFSC niche or molecular signaling across adjacent HF across the tissue (Widelitz & Chuong, ; Gonzales & Fuchs, ; Guasch, ). Here, we now show that within a single HF, HFSC associates with LV capillaries, starting from developmental HF stages.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally well‐acknowledged that HFSC creates a special niche microenvironment, where the interactions with other cells within the niche are important for HFSC organization and function (Gonzales & Fuchs, ; Guasch, ). In this regard, we observed that a functional HFSC niche is required to sustain the polarized LV–HF association in the back skin, through the expression of Wnt ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative evidence supports multiple possible mechanisms of epidermal homeostasis: 1) a hierarchical lineage of relatively quiescent stem cells giving rise to faster cycling, committed progenitor cells that then exit the cell cycle and terminally differentiate; 2) a single, equipotent population of progenitor cells stochastically choosing between self-renewal and differentiation; and 3) two spatially segregated populations of stem cells that divide at different rates and adopt distinct lineage trajectories (Gonzales and Fuchs, 2017;Mascré et al, 2012;Rompolas et al, 2016;Sada et al, 2016). The different criteria used for stem/progenitor fate assignment (often linked to the specific techniques used), such as molecular differentiation markers, basal layer residence status, and assumptions about stem-cell-division or clonal-growth kinetics, may account for the differences in data interpretation (Gonzales and Fuchs, 2017). Moreover, the observed epidermal stem cell heterogeneity in mouse back skin may reflect different cellular states of a single differentiation program (Rognoni and Watt, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Within the adult mouse interfollicular epidermis, stem/progenitor cells residing in the basal layer undergo self-renewing or differentiative cell divisions to maintain a proper pool of basal cells and to generate post-mitotic differentiating (spinous, granular) cells in the suprabasal layers that ultimately form the stratum corneum -an outer permeability barrier that protects an organism from dehydration, infection, and a myriad of other harmful insults (Gonzales and Fuchs, 2017). Cumulative evidence supports multiple possible mechanisms of epidermal homeostasis: 1) a hierarchical lineage of relatively quiescent stem cells giving rise to faster cycling, committed progenitor cells that then exit the cell cycle and terminally differentiate; 2) a single, equipotent population of progenitor cells stochastically choosing between self-renewal and differentiation; and 3) two spatially segregated populations of stem cells that divide at different rates and adopt distinct lineage trajectories (Gonzales and Fuchs, 2017;Mascré et al, 2012;Rompolas et al, 2016;Sada et al, 2016). The different criteria used for stem/progenitor fate assignment (often linked to the specific techniques used), such as molecular differentiation markers, basal layer residence status, and assumptions about stem-cell-division or clonal-growth kinetics, may account for the differences in data interpretation (Gonzales and Fuchs, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The continuous renewal of the stratum corneum and eventually of the complete keratinocyte compartment of the epidermis limits damage and infections and allows to respond to environmental impacts by adapting the structure and biological activity of the epidermis. The switch from normal epidermis under homeostasis to hyperkeratotic epidermis in wound healing and inflammation is crucial for the remarkable tolerance of the skin towards local damage …”
mentioning
confidence: 99%